2022
DOI: 10.34133/2022/9758408
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic and Mental Health Concerns on Twitter in the United States

Abstract: Background. During the COVID-19 pandemic, mental health concerns (such as fear and loneliness) have been actively discussed on social media. We aim to examine mental health discussions on Twitter during the COVID-19 pandemic in the US and infer the demographic composition of Twitter users who had mental health concerns. Methods. COVID-19-related tweets from March 5th, 2020, to January 31st, 2021, were collected through Twitter streaming API using keywords (i.e., “corona,” “covid19,” and “covid”). By further fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Consistent with research on similar topics, we found that COVID-19 has severely impacted public mental health and has dynamic influences on public mental health [30,42]. In addition, we found that the proportion of anxiety-related tweets increased to a substantial peak in March 2020 and remained low but stable for several months.…”
Section: Comparison To Prior Worksupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with research on similar topics, we found that COVID-19 has severely impacted public mental health and has dynamic influences on public mental health [30,42]. In addition, we found that the proportion of anxiety-related tweets increased to a substantial peak in March 2020 and remained low but stable for several months.…”
Section: Comparison To Prior Worksupporting
confidence: 86%
“…Meanwhile, Berry et al [29] pointed out through a study with both quantitative and qualitative approaches that people are willing to discuss mental health problems on Twitter for varied reasons, including the sense of community and Twitter being a safe space for expression, coping, empowerment, etc. However, existing literature on public mental health during the pandemic using Twitter data [30][31][32][33] either has short study periods and small sample sizes or does not focus on subtypes of mental health problems and subgroup prevalence. More granular study designs and more comprehensive data are needed for such studies.…”
Section: Introductionmentioning
confidence: 99%
“…Digital modernity also received the mother of all exogenous pushes when the COVID-19 pandemic made offline interaction riskier, and often illegal, accelerating the migration online (indeed, the development of e-commerce in Eastern Asia was kick-started in the first place by the smaller-scale disruption of the SARS epidemic of 2002-04). And with the quantity of data created and the increased amount of processing required, the cloud, or more accurately clouds, are only going to grow in the medium term -especially given the successes, failures and potential of the ambient data infrastructure in combating COVID-19 itself, for example in data science (Dayan et al, 2021;Podder et al, 2021), epidemiology (Khakharia et al, 2021;Rahimi et al, 2021), tracking and tracing (Abbas and Michael, 2020), and monitoring public attitudes (Perrotta et al, 2021;Zhang et al, 2022). Of course, it was also used for misinformation (Brennen et al, 2020;Shahi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It collects data through the network to observe human psychology and behavior (36,37). At present, researchers have used this method to measure the public's reaction to government policies such as mental health and social prejudice (38,39). In the aspect of emotional attitude research, we also began to use this method to carry out relevant research (40).…”
Section: Introductionmentioning
confidence: 99%